2009
DOI: 10.2478/v10042-008-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic stem cells.

Abstract: Both skeletal muscle and bone marrow tissue contain myogenic stem cells. The population residing in muscles is heterogenic. Predominant in number are "typical" satellite cells -muscle progenitors migrating from somites during embryonic life. Another population is group of multipotent muscle stem cells which, at least in part, are derived from bone marrow. These cells are tracked by gradient of growth factors releasing from muscle during injury or exercise. Recruited bone marrow-derived cells gradually change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 87 publications
(135 reference statements)
0
8
0
1
Order By: Relevance
“…Therefore, it can be concluded that isolated population predominantly consisted of myoblasts. However, as heterogeneity of the population isolated from skeletal muscle tissue is well known [25], we’d rather call the obtained population "muscle-derived cells". Bone marrow-derived cells, typically for a MSC population, displayed multilineage differentiation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that isolated population predominantly consisted of myoblasts. However, as heterogeneity of the population isolated from skeletal muscle tissue is well known [25], we’d rather call the obtained population "muscle-derived cells". Bone marrow-derived cells, typically for a MSC population, displayed multilineage differentiation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term culturing of human muscle‐derived cells promotes the expression of phenotypic and functional markers typical for mesenchymal stem cells (Lecourt et al, ). According to the expression of stem cell markers, CD34 and Sca‐1, our established cell lines may contain MDSC (Usas and Huard, ; Burdzińska et al, ; Wu et al, ). Moreover, distinct proportions of stem cell subpopulations at different maturation stages may exist at different times and under different conditions in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Burdzinska et al [139] suggested a relationship between bone-marrow derived stem cells, multipotent muscle stem cells and satellite cells. In this proposed model, both MSC and HSC are released from the bone marrow to peripheral blood in response to certain stimuli such as exercise or skeletal muscle injury.…”
Section: Skeletal Musclementioning
confidence: 99%